Development of high school biology student worksheets based on critical thinking skills on the coordination system concept - Sinta Damayanti; Muhammad Zaini; Bunda Halang (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Lack of critical thinking skills of students is one of the problems in education. One of the learning tools that need to be improved in order to improve critical thinking skills is the Student Worksheet (LKPD). This study aims to describe the validity of LKPD on the concept of a Coordination System Based on Critical Thinking Skills. This method uses a type of research, namely EDR (Educational Design Research) with reference to Tessmer's formative evaluation which consists of two stages, namely 1) Self-evaluation; and 2) Expert review. The Critical Thinking Skills used in this study refer to Facione. The subject of validation was two experts, namely lecturers. This type of research is a development research to produce a valid product. The results of this study indicate that the validity of LKPD based on expert tests has a valid category with an overall average of 3.41.Abstrak Kurangnya keterampilan berpikir kritis peserta didik didik merupakan salah satu permasalahan dalam pendidikan. Salah satu perangkat pembelajaran yang perlu diperbaiki agar meningkatkan keterampilan berpikir kritis ialah Lembar Kerja Peserta Didik (LKPD). Penelitian ini bertujuan untuk mendeskripsikan validitas LKPD pada konsep Sistem Koordinasi Berbasis Keterampilan Berpikir Kritis. Metode ini menggunakan jenis penelitian yaitu EDR (Educational Design Research) dengan mengacu pada evaluasi formatif Tessmer yang terdiri dari dua tahapan yaitu 1) evaluasi diri; dan 2) pendapat ahli. Keterampilan Berpikir Kritis yang digunakan dalam penelitian ini mengacu pada Facione. Subjek validasi adalah dua orang ahli yaitu dosen. Jenis penelitian ini merupakan penelitian pengembangan untuk menghasilkan produk yang valid. Hasil penelitian ini menunjukkan bahwa validitas LKPD berdasarkan uji pakar memiliki kategori valid dengan rata-rata keseluruhan 3,41.